2008
DOI: 10.1002/ijc.24030
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy at a late stage enhances imatinib‐induced cytotoxicity in human malignant glioma cells

Abstract: Malignant gliomas are common primary tumors of the central nervous system. The prognosis of patients with malignant glioma is poor in spite of current intensive therapy and thus novel therapeutic modalities are necessary. Imatinib mesylate, a tyrosine kinase inhibitor, is effective in the therapy of tumors including leukemias but not as a monotherapy for malignant glioma. Recently, it is thought that the adequate modulation of autophagy can enhance efficacy of anticancer therapy. The outcome of autophagy manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
111
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(120 citation statements)
references
References 40 publications
7
111
1
1
Order By: Relevance
“…Several important anticancer agents, including arsenic trioxide, 5-FU, tamoxifen, imatinib, paclitaxel and cisplatin , has been shown to induce atutophagy in a few types of cancer cells (Bursch et al, 1996;Paglin et al, 2001;Carew et al, 2007;Shingu et al, 2009;Goussetis et al, 2010;Liu et al, 2011;Xi et al, 2011;Yang et al, 2011). In the present study, we have demonstrated that autophagy is also induced in glioblastoma cells during the course of GA treatment.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Several important anticancer agents, including arsenic trioxide, 5-FU, tamoxifen, imatinib, paclitaxel and cisplatin , has been shown to induce atutophagy in a few types of cancer cells (Bursch et al, 1996;Paglin et al, 2001;Carew et al, 2007;Shingu et al, 2009;Goussetis et al, 2010;Liu et al, 2011;Xi et al, 2011;Yang et al, 2011). In the present study, we have demonstrated that autophagy is also induced in glioblastoma cells during the course of GA treatment.…”
Section: Discussionsupporting
confidence: 64%
“…The induction of these two different types of autophagy may depend on different stimuli and cell types. Although the exact mechanisms of the two autophagy are not clear, it seems that the suppression of cytoprotective autophagy and the enhancement of cytotoxic autophagy might augment cytotoxic effects of anticancer drugs (Kanzawa et al, 2004;Takeuchi et al, 2005;Shingu et al, 2009;Pandey and Chandravati, 2012). In this study, we found that GA induced an apparent autophagy in GBM cells, and inhibition of autophagy could lead to enhancement of GA-mediated cytotoxicity through increasing apoptosis.…”
Section: Autophagy Inhibition Promotes Gambogic Acid-induced Suppressmentioning
confidence: 58%
“…Moreover, inhibition of autophagy by BAF enhanced imatinib induced-cytotoxicity. 34 Although our study as well as other previous studies have observed that the inhibition of autophagy with BAF in the late stage increased the caspase-9 activity and autophagy was inhibited with sh-BECN1 (Fig. 3E, red).…”
Section: Discussionsupporting
confidence: 53%
“…Recently, some studies have reported that inhibiting autophagy with BAF boosts the cytotoxicity of cancer therapeutic agents. 19,34 Our results showed that MCF-7 cells exhibited significant toxic effects after exposure to 5, 10 and 20 nM BAF over 24 h, while no toxic effects were detected when exposed to 1 nM BAF for 72 h (Fig. 4A).…”
Section: Discussionmentioning
confidence: 76%
“…18 Not surprising, autophagy has been shown to have an active role in cancer development and progression, 19,20 as well as in the cytotoxic response to anticancer drugs. [21][22][23][24] In T lymphocytes autophagy has been implicated in survival and cytokine-induced proliferation, as well as in cell death after growth factor-withdrawal. 25,26 The expression level of beclin-1 changes during T and B lymphocyte maturation and T-cell activation.…”
mentioning
confidence: 99%